Consent for blood transfusion. (24th August 2010) - Farrell, Anne-Maree; Brazier, Margaret
Abstract : Millions of people receive blood transfusions each year, but many will not be fully aware of the risks. Anne-Maree Farrell and Margaret Brazier argue for a formalised consent procedure